Ukraine at the European Crossroads New Opportunities and Challenges while Acquiring Practical Competencies & Skills Within The Collaborative Teaching Project DOEU. - Bohatyrets, Valentyna; Хавлін, Тетяна (Технодрук, 2021)
In our talk, we reflected on the EU-funded Jean-Monnet module «Doing Europe – Cohesion and Integration in the EU» (JMM Do EU), in the period between 2019 and 2022. This Module is experimental, and based on collaborative teaching and brings together students from the University of Siegen in Germany and Yuriy Fedkovych Chernivtsi National University in Ukraine. The project Doing Europe (DoEU) relies on the constructivist approach to understanding social, political and cultural processes within the EU and Europe in the broader sense and their relevance in the Ukrainian context. Such an approach deals critically with the multiplicity of existing conceptual and historical interpretations of Europe.
УКРАЇНА НА ПЕРЕХРЕСТІ ЄВРОПИ: НОВІ МОЖЛИВОСТІ ТА ВИКЛИКИ НАБУТТЯ ПРАКТИЧНИХ КОМПЕТЕНЦІЙ І НАСКРІЗНИХ НАВИЧОК ПІД ЧАС СЛУХАННЯ ПРОЄКТУ ЖАНА МОНЕ «DOEU»
Keywords: Doing Europe; the EU; Ukraine; higher education; collaborative teaching; students’ engagement; crosscutting skills and competences